Characteristics and advances in signaling pathways, cellular communication, cell junctions, and oxidative stress in lymphedema - Zhao, Qiancheng; Niu, Zhipu; Pan, Ying; Hao, Yongqi; Ma, Yuan; Zhao, Jiankai; Du, Jianshi; Yang, Yiming (Frontiers in Cell and Developmental Biology, 2025)
Lymphedema is a chronic inflammatory disease without an effective treatment method, and it results in a high disease burden and psychological distress in patients. Although there have been significant advances in targeted therapies, there are still no effective options to treat this refractory disease. In recent years, new advances and breakthroughs have been made in signaling pathways, including RAS/MAPK, PI3K/AKT, VEGF-C/VEGFR-3, HGF/MET, and TGF-β1, which are important for understanding the pathogenesis and disease progression of lymphedema. Mutations in genes encoding cell junctions affect the formation of junctions in lymphatic endothelial cells (LECs), causing abnormal lymphatic valve development and the impairment of lymphatic vessels. A vicious cycle of oxidative stress and chronic inflammation of lymphatic vessels leads to lymphedema. Moreover, the interactions and information communication of T-cell subsets, neutrophils, macrophages, dendritic cells (DCs), and fibroblasts with LECs play equally important roles in the progression of lymphedema. Therefore, this paper summarizes the reported signaling pathways, cell junctions, oxidative stress, and cell communication involved in lymphedema, with the goal of providing ideas and a basis for understanding the pathogenesis, disease progression and targeted therapy of lymphedema. By integrating current findings on signaling dysregulation, cell junctions, and cellular crosstalk, this review provides a conceptual framework for developing multitarget therapeutic strategies to restore lymphatic homeostasis and develop potential therapies for treating lymphedema.